Acid hydrolysis of almond shells in a biphasic reaction system: Obtaining of purified hemicellulosic monosaccharides in a single step. (September 2021) - Dávila, Izaskun; Diaz, Estelle; Labidi, Jalel
Graphical abstract: Highlights: Lignin-PVA smart hydrogels were successfully synthesized. Medium and high molecular weight PVA enabled a good synthesis. Lignin-PVA hydrogels presented high swelling capacities and reusability. The smart hydrogels were pH and temperature responsive. Lignin enhanced the adsorption of methylene blue cationic dye. Abstract: The aim of this work is to comprehend the biphasic reaction systems through another perspective; the simultaneous purification and production of carbohydrates during the pretreatment of biomass. A dilute acid hydrolysis of almond shells in a 2-Methyltetrahydrofuran/H2 O system was optimised to maximise the obtaining of hemicellulose-derived monosaccharides with the minimum formation of degradation products. The optimised conditions of the biphasic reaction system, which produced 205.3 g hemicellulose-derived monosaccharides/Kg almond shells, were replicated in a monophasic reaction system to assess the benefits of the biphasic reaction systems. The latest system allowed the removal of 85.3% of the furans generated during the dilute acid hydrolysis, creating antioxidant extract, together with the catalysis of the hydrolysis of the hemicelluloses in a 20%. Therefore, the proposed process could become a promising method to purify carbohydrates with an environmentally friendly procedure that allowed the obtaining of multiple added-value products in a single step.